2010
DOI: 10.1136/jnnp.2009.193391
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of clinical diagnosis in tremulous parkinsonian patients: a blinded video study

Abstract: We found a high false positive (17.4 to 26.1%) and negative rate (6.7 to 20%) for the diagnosis of PD. The diagnostic distinction of TDPD from dystonic tremor was reduced by the presence of dystonic features in treated and untreated PD patients.Clinical distinction of TDPD from atypical tremor, monosymptomatic rest tremor, and dystonic tremor can be difficult, due to the presence of parkinsonian features in tremulous SWEDD patients. The diagnosis of bradykinesia was particularly challenging. This study highlig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 37 publications
3
69
0
3
Order By: Relevance
“…It has been suggested that SWEDD subjects may have a dystonic tremor masquerading as PD, but it is uncertain whether the tremor in any of the PRE-CEPT subjects had those characteristics. 20,21 The change in diagnosis from idiopathic PD at baseline to a PP alternative at study termination in 44% of SWEDD subjects compared with 3.7% of those with DAT deficit [ 123 I] b-CIT scans at baseline again demonstrates that the SWEDD group differs from those with baseline DAT deficit scans. Based on investigator report, the baseline SWEDD subjects with a final diagnosis of PP were less likely to manifest tremor, bradykinesia, and rigidity than those with a DDP diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that SWEDD subjects may have a dystonic tremor masquerading as PD, but it is uncertain whether the tremor in any of the PRE-CEPT subjects had those characteristics. 20,21 The change in diagnosis from idiopathic PD at baseline to a PP alternative at study termination in 44% of SWEDD subjects compared with 3.7% of those with DAT deficit [ 123 I] b-CIT scans at baseline again demonstrates that the SWEDD group differs from those with baseline DAT deficit scans. Based on investigator report, the baseline SWEDD subjects with a final diagnosis of PP were less likely to manifest tremor, bradykinesia, and rigidity than those with a DDP diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…These patients could represent an important subgroup of patients suspected clinically to have early PD, but who have scans without evidence of dopaminergic deficit (SWEDD). It can be difficult to distinguish these patients from those with PD on clinical grounds, but SWEDD cases can present with atypical or dystonic tremor (Bajaj et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…They feature no compromised presynaptic function over years, no progressive decline of presynaptic functions, a lack of a clear positive response to dopaminergic medication (an exception may be some patients with dopa-responsive dystonic tremor), and no patterns of glucose metabolism compatible with classic PD. The prognosis of SWEED subjects is considered to be more favorable than that for classic neurodegenerative PS (32)(33)(34)(35)(36). To the best of our knowledge, histopathologic proof of SWEDD pathology is still lacking; for further clarification, such studies are clearly needed.…”
Section: Sweddsmentioning
confidence: 99%
“…Thus, the comprehensive appraisal of presynaptic DAT imaging is focused on the question of whether symptoms in a patient might be related to neurodegeneration. This question is frequently the diagnostic challenge for the neurologist in the clinical setting, as studies have indicated that a disease-particular in its early stage-that is not associated with neurodegeneration, such as the various tremor syndromes (including ET); drug-induced, psychogenic, and vascular PS; or even Alzheimer dementia, may be misdiagnosed as a neurodegenerative PS (32,45,46).…”
Section: Proof Of Symptomatic Parkinsonismmentioning
confidence: 99%